2020
DOI: 10.1186/s13041-020-00628-y
|View full text |Cite
|
Sign up to set email alerts
|

Drp1 is widely, yet heterogeneously, distributed in the mouse central nervous system

Abstract: Objectives: Drp1 is widely expressed in the mouse central nervous system and plays a role in inducing the mitochondrial fission process. Many diseases are associated with Drp1 and mitochondria. However, since the exact distribution of Drp1 has not been specifically observed, it is difficult to determine the impact of anti-Drp1 molecules on the human body. Clarifying the specific Drp1 distribution could be a good approach to targeted treatment or prognosis. Methods: We visualized the distribution of Drp1 in dif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 52 publications
(68 reference statements)
3
3
0
2
Order By: Relevance
“…In mammalian cells, ssion/fusion events are mainly mediated by several large dynaminrelated GTPase proteins, including conserved dynamin-related GTPase (Drp1), conserved dynamin-related GTPase mitofusion 1 and 2 (Mfn1 and 2), and optic dominant atrophy 1 (Opa1). Our lab have published the data previously about the expression of Drp1 at high level on the soma of cerebellum Purkinje cells by the combination of immunohistochemistry and in situ hybridization on GAD67 (glutamic acid decarboxylase 67) -GFP (green uorescent protein) transgenic mice (Luo TT et al, 2020). The present ndings have con rmed the distribution pattern of Drp1 on Purkinje cells.…”
Section: Drp1/mfn1/mfn2supporting
confidence: 79%
“…In mammalian cells, ssion/fusion events are mainly mediated by several large dynaminrelated GTPase proteins, including conserved dynamin-related GTPase (Drp1), conserved dynamin-related GTPase mitofusion 1 and 2 (Mfn1 and 2), and optic dominant atrophy 1 (Opa1). Our lab have published the data previously about the expression of Drp1 at high level on the soma of cerebellum Purkinje cells by the combination of immunohistochemistry and in situ hybridization on GAD67 (glutamic acid decarboxylase 67) -GFP (green uorescent protein) transgenic mice (Luo TT et al, 2020). The present ndings have con rmed the distribution pattern of Drp1 on Purkinje cells.…”
Section: Drp1/mfn1/mfn2supporting
confidence: 79%
“…In mammalian cells, ssion/fusion events are mainly mediated by several large dynaminrelated GTPase proteins, including conserved dynamin-related GTPase (Drp1), conserved dynamin-related GTPase mitofusion 1 and 2 (Mfn1 and 2), and optic dominant atrophy 1 (Opa1). Our lab have published the data previously about the expression of Drp1 at high level on the soma of cerebellum Purkinje cells by the combination of immunohistochemistry and in situ hybridization on GAD67 (glutamic acid decarboxylase 67) -GFP (green uorescent protein) transgenic mice [24]. The present ndings have con rmed the distribution pattern of Drp1 on Purkinje cells.…”
Section: Drp1/mfn1/mfn2supporting
confidence: 79%
“…According to our previous report [24], we demonstrated that Drp1 was overexpressed in the cerebellum Purkinje layer, while Drp1 and GAD67 also colabeled well in this area. Drp1 and GAD67 colabeling was lower in other nuclei.…”
Section: Drp1 (Green) and Mcu (Red)supporting
confidence: 65%
“…Our previous study has shown that Drp1 is highly expressed at the spinal cord level [ 33 ]. And many studies have shown different NP contributed to the increased expression of Drp1 [ [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] ].…”
Section: Resultsmentioning
confidence: 99%
“…The dynamin family of large GTPases regulates mitochondrial membrane dynamics in all eukaryotes: Drp1 for fission, and mitofusins (Mfn1/2) and optic atrophy-1 (Opa1) for fusion [ [20] , [21] , [22] , [23] ]. Our own study has shown that Drp1 is distributed all over the whole nervous system, especially high at the spinal cord level [ 33 ]. In different NP model, Drp1 expression or its phosphorylated state is reported to either increase or decrease.…”
Section: Discussionmentioning
confidence: 99%